Lithium‐Ion Battery Thermal Management Techniques and Their Current Readiness Level. Issue 1 (26th October 2022) - Rana, Suraj; Kumar, Rajan; Bharj, Rabinder Singh
Abstract : The lithium‐ion battery (LiB) is currently an essential part of electric vehicles (EVs). The popularity of LiBs among EV manufacturers is because of their long life, fewer memory effects, high specific energy density, and lightweight. However, temperature affects the LiB life and performance to a great extent. The burden on battery thermal management (BTM) is significantly increased by the need to increase battery capacity and decrease the battery charging time. Hence, reliable and effective BTM is the need of the hour. Herein, the current status of different battery cooling techniques has been discussed along with their merits and demerits. The main objective of this paper is to inform the readers and give them a clear understanding of various cooling techniques and their current status and highlight any novel approaches being used by the researchers to improve these cooling techniques. Future needs and opportunities in this field have also been discussed. Abstract : The primary goal of this study is to enlighten readers on the current status of various battery thermal management techniques and highlight any novel approaches being used by the researchers to improve these techniques. The merits and demerits of these techniques along with future needs and opportunities in this field have also been discussed.